La problemática de lo ético-político en Mille plateaux - Díaz, Luis Omar (2015)
The present contribution aims to clarify the ethics involved in the notionof territory, coined by Deleuze and Guattari in Mille plateaux, whose philosophical notes are taken from Spinoza’s and Nietzsche’s works. We will see that this project is sufficiently consistent and united, according to its immanent and materialistic lines. However, this ethics finds its limits, not in its internal constitution but in its tacit iden- tification with politics. Our authors conceive the existential field as crossed by political effects, therefore, all ethical acts would be, by their accounts, a political act too. And these acts will be the more perfect –more ethical and more political– the less they deal with traditional state policy. This involves reducing policy to the political, which we believe is a mistake; because, what applies to the singular-collective existence cannotcount nor compete as a substitute of the collective institutional policy.